Chapel of inadvertent joy - McDaniel, Jeffrey, 1967- (Pitt poetry series., 2013)
[This book of poetry] was written by a master of metaphor and a poet of huge imagination and fierce ingenuity, a fine antidote to realism. -- Major Jackson.